Автоматизація архівної діяльності сервісу експрес-доставки "Нова пошта" - Білущак, Тетяна; Постоєнко, Валерія (Видавництво Львівської політехніки, 2017)
Automated information system actively implementing activities in enterprises. In order to reduce the time and carry out further development of express delivery service "Novaposhta" necessary to apply automati on archival activities. This will help optimize many offices service "Novaposhta".
Keywords: інформація; підприємство; інформаційне суспільство; архівна справа; інформаційна система; інформаційні технології; автоматизована інформаційна система